Analisis Strategis Pengelolaan Keuangan pada Keluarga Milenial - Ferry Noviandy; Reza Pahlevi; Angga Permadi Kapriana (Universitas Muhammadiyah Pontianak, 2026)
Financial technology offers opportunities and risks for Millennial household financial management. This study analyzes financial management strategies, technology use, and factors affecting household financial stability. Using a descriptive qualitative design, participants were selected purposively; data were collected through in-depth interviews and analyzed using the Miles, Huberman, and Saldaña model. Millennial families-maintained stability through budgeting, expenditure control, record-keeping, and emergency funds. Their practices were shaped by financial literacy, income, lifestyle, social environment, and technology use. The findings highlight the need to integrate financial literacy, self-control, and prudent technology used to sustain family financial stability. Keywords: Millennials; Family Financial Management; Financial Technology; Financial Literacy; Behavioral Finance; Digital Era; Household Financial Stability